2014
DOI: 10.1160/th13-05-0384
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor versus prasugrel in diabetic patients with an acute coronary syndrome

Abstract: Optimal P2Y12 receptor blockade is critical to prevent ischaemic recurrence in patients undergoing percutaneous coronary intervention (PCI). We aimed to compare the level of platelet reactivity (PR) inhibition achieved by prasugrel and ticagrelor loading dose (LD) in diabetic acute coronary syndrome (ACS) patients undergoing PCI. We performed a single-center prospective open-label randomised trial. Patients with diabetes mellitus undergoing PCI for an ACS were randomised to receive prasugrel 60 mg or ticagrelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 29 publications
4
47
1
Order By: Relevance
“…Small pharmacodynamic studies have demonstrated very low rates of HTPR in ticagrelor-treated patients, immediately after ACS and into the maintenance phase [9][10][11]. Consistently, in a small series of patients with ACS, we recently reported significantly reduced platelet reactivity with ticagrelor compared with prasugrel up to 30 days after PCI [12].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Small pharmacodynamic studies have demonstrated very low rates of HTPR in ticagrelor-treated patients, immediately after ACS and into the maintenance phase [9][10][11]. Consistently, in a small series of patients with ACS, we recently reported significantly reduced platelet reactivity with ticagrelor compared with prasugrel up to 30 days after PCI [12].…”
Section: Introductionsupporting
confidence: 73%
“…Two-hours after antiplatelet loading for primary PCI, the rapid activity of platelet inhibitor drugs (RAPID) study showed that rates of prasugrel was non-inferior to ticagrelor in terms of rates of HTPR [9]. On-treatment platelet reactivity up to 18 h after loading was lower in ticagrelor-treated patients compared to prasugrel in diabetic patients presenting with ACS [11]. In ACS patients who experienced HTPR on clopidogrel, 2-weeks of treatment with ticagrelor appeared to significantly reduce platelet reactivity compared with prasugrel [10].…”
Section: Ticagrelor and Platelet Reactivitymentioning
confidence: 99%
“…However, both studies did not show any differences in HPR rates. 28,29 Indeed, our study results showing that prasugrel and ticagrelor reach overall nonsignificantly different levels of platelet inhibition in both the acute and chronic phases of treatment did not completely confirm these findings. This may be attributed to some methodological differences of these studies, such as the use of a single PD assay, the lack of double blinding, and the lack of evaluation of both the acute and maintenance phases of therapy.…”
contrasting
confidence: 61%
“…26,27 Nonetheless, data in patients with DM, who are characterized by a unique prothrombotic milieu, are still limited. A study by Laine et al 28 assessing the acute effects of ticagrelor versus prasugrel in DM patients showed that ticagrelor was associated with lower PRI levels measured by VASP (6-18 hours after LD). A study by Alexopoulos et al 29 assessing the chronic effects of these agents in DM patients showed that ticagrelor was associated with lower PRU levels measured by VN-P2Y12 (2-4 hours after MD).…”
mentioning
confidence: 99%
“…Both deoxycoformycin and ticagrelor have already been used in clinical trials with T1D or acute coronary syndrome patients, showing some beneficial effects related to renovascular diabetic complications, e.g. reduced albuminuria and platelet activation (Aizawa et al, 1990;Bonello et al, 2014;Laine et al, 2014). In addition to diabetes and cardiovascular disease, alternative strategies for increasing locally adenosine levels are tested in epilepsy.…”
Section: Indirect Receptor Targetingmentioning
confidence: 99%